Reading the Smoked Fish MSME Market Competition Map Through Analysis of Porter's Five Forces of Perception - Apriliyanto, Yohandika Tri; Khasanah, Sufrotun; Ashidik, Beta Arya (Innovation, Technology, and Entrepreneurship Journal, 2024)
Fisheries are a superior commodity and are still a favorite on the world market. Processed seafood that is quite interesting to discuss is smoked fish. The smoking activity itself provides several benefits, including: providing a preservation effect on fish meat, improving the taste of fish, and utilizing excess catches during the abundant fishing season. In the journey of Smoked Fish UMKM, of course there are various obstacles faced, including decreased turnover, lack of technological capabilities and marketing networks. Porter's Five Forces can be used to identify industry-specific competitive strategies for businesses. For Jrakahpayung smoked fish MSMEs to overcome the challenging competitive environment, competitive strategy planning is very helpful. Based on the analysis, Jrakahpayung smoked fish MSMEs are not too affected by the threats posed by business competitors because there are only a few comparable MSMEs. However, because the quality of the raw materials used must always be maintained so that consumers are loyal to Jrakahpayung smoked fish products, the threat to buyers and suppliers is quite high. On the other hand, consumer purchasing power automatically decreases if suppliers do not provide high quality raw materials. The total value of the threat of new entrants is 2.4 medium, the bargaining power of buyers is 3.5 high, the threat of substitutes is 1.9 low, the bargaining power of suppliers is 4.8 high, competition between existing competitors is 2.4 medium.